The difference between democracy as a system and democracy as a principle - Mohamad Shukri, Syaza Farhana (2020)
As the political battle waged on among supporters of both sides, there are those who accused some Malaysians to be disrespectful of the Yang diPertuan Agong's decision. They say that it is due to the Agong’s wisdom that we were able to move past the impasse and thus proves the resilience of Malaysia’s democracy. No